Realization of walnut‐shaped particles with macro‐/mesoporous open channels through pore architecture manipulation and their use in electrocatalytic oxygen reduction - Guan, Bu Yuan (2020)
Herein we report a simple dual‐soft‐template approach to prepare walnut‐shaped macro‐/mesoporous polydopamine particles with diameter of ca. 270 nm, highly accessible bicontinuous channels and wide pore size distribution from ca. 20 nm to ca. 95 nm. This approach provides great opportunities to tailor the soft template‐directed assembly processes and generate various polydopamine particles with controllable mesophase curvature. Walnut‐shaped mesoporous carbon particles with large open mesochannels in the range of ca. 13 nm to ca. 50 nm can be fabricated by subsequent thermal treatment under nitrogen atmosphere. Lastly, we demonstrate that the as‐derived walnut‐shaped carbon particles manifest enhanced electrocatalytic performance for oxygen reduction reaction in alkaline electrolyte.